STUDENTS’ CHALLENGES IN ONLINE ENGLISH SYNCHRONOUS LEARNING THROUGH GOOGLE MEET - Suaib, Nurul Afiah; Nappu, Syamsiarna; Sangkala, Ismail (FKIP Unismuh Makassar, 2022)
This research aimed at finding out the students’ challenges on the synchronous learning through Google Meet focused on online English learning. The researcher used descriptive qualitative research as research. The population of this research was the students at the eight-grade students of SMPN 1 Bontonompo who have been learning online synchronous learning through Google Meet. Ten students were chosen for the study using a purposive selection approach. Semi-structural interviews were used in this study. The findings of the research indicated that there were challenges and difficulties associated with English online learning via Google Meet, which was implemented at SMPN 1 Bontonompo. These challenges and difficulties included unstable internet connections during learning, limited learning media due to students' lack of laptops or smartphones, limited time and techniques for providing online explanations, and students who did not comprehend the material during online learning. As a result, it can be stated that the online learning process presents certain difficulties for those who do not comprehend the subject offered. Some of the students who did not get a signal struggled to comprehend the content during the learning process, and the instructor was also unable to immediately communicate the students' comprehension of the teacher-provided material. The findings of solution for English students to face the challenges of online learning through Google Meet is to keep trying their best following online learning and following the rules and decisions of their respective teachers because studying in the classroom with the teacher directly cannot be replaced by anything